Multidisciplinary treatment of radicular cyst caused by delayed trauma in the maxillary central teeth – case report - Nihal Altunok Ünlü; Ahmet Altan; Halenur Altan (Journal of Pre-Clinical and Clinical Research, 2021)
Objective The aim of this case report is to present a multidisciplinary treatment administered to a patient with a cystic lesion in the jawbone, in the root region of the incisors, caused by trauma. The report also emphasizes the effect of accurate diagnosis and treatment planning on the prognosis of cyst-associated teeth in the presence of large cystic lesions.